Extent of Surgical Resection in Lower-Grade Gliomas: Differential Impact Based on Molecular Subtype - Patel, S.H. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Diffuse lower-grade gliomas are classified into prognostically meaningful molecular subtypes. We aimed to determine the impact of surgical resection on overall survival in lower-grade glioma molecular subtypes. MATERIALS AND METHODS: For 172 patients with lower-grade gliomas (World Health Organization grade II or III), pre- and postsurgical glioma volumes were determined using a semiautomated segmentation software based on FLAIR or T2-weighted MR imaging sequences. The association of pre- and postsurgical glioma volume and the percentage of glioma resection with overall survival was determined for the entire cohort and separately for lower-grade glioma molecular subtypes based on isocitrate dehydrogenase (IDH) and 1p/19q status, after adjustment for age, sex, World Health Organization grade, chemotherapy administration, and radiation therapy administration. RESULTS: For the entire cohort, postsurgical glioma volume (hazard ratio, 1.80; 95% CI, 1.18–2.75; P = .006) and the percentage of resection (hazard ratio, 3.22; 95% CI, 1.79–5.82; P < .001) were associated with overall survival. For IDH-mutant 1p/19q-codeleted oligodendrogliomas, the percentage of resection (hazard ratio, 6.69; 95% CI, 1.57–28.46; P = .01) was associated with overall survival. For IDH-mutant 1p/19q-noncodeleted astrocytomas, presurgical glioma volume (hazard ratio, 3.20; 95% CI, 1.22–8.39; P = .018), postsurgical glioma volume (hazard ratio, 2.33; 95% CI, 1.32–4.12; P = .004), and percentage of resection (hazard ratio, 4.34; 95% CI, 1.74–10.81; P = .002) were associated with overall survival. For IDH-wild-type lower-grade gliomas, pre-/postsurgical glioma volume and percentage of resection were not associated with overall survival. CONCLUSIONS: The extent of surgical resection has a differential survival impact in patients with lower-grade gliomas based on their molecular subtype. IDH-mutant lower-grade gliomas benefit from a greater extent of surgical resection, with the strongest impact observed for IDH-mutant 1p/19q-noncodeleted astrocytomas.